Evaluating teaching presence in a virtual environment : examining interactions in a forum of the PROEDI social Network - Lisbôa, Eliana Santana (2012)
With the spread of Internet and digital technologies the discussion forums usage in informal spaces, as for example in virtual social networks, became a strategy which aims to establish and strengthen the social bonds between teachers/students and students/students and, above all, promote collaborative learning. Based mainly in a form of asynchronous communication, the use of the forum allows complementing activities in the classroom through social, cognitive and teaching presence. The presence of teaching, considered in the literature as the most important of the three in online learning, has as main objective to promote an environment where knowledge sharing and the increase of construction of meanings within the community. It is in this context where the present study fits, whose objective is to assess the presence of teaching in the social network forum PROEDI (Teachers in the Digital Era – www.proedi.ning.) entitled "The importance of Educational Technologies" and that was applied to a group of prospective teachers who attended a master's degree in Education from the University of Minho. The results obtained in the analysis of the contributions posted came to prove that the role of the e-moderator has fallen far short of the initially expected since their participation was very shy when it comes to mobilize and encourage students to participate in discussions and also to socialize knowledge. However, the results obtained also led us to conclude that the presence of teaching in a social network can happen not necessarily associated with the effective intervention of the e-moderator, but as a result of the involvement and willingness of students to learn.